Up periscope [videorecording (DVD)] - Schenck, Aubrey, 1908-1999; Douglas, Gordon, 1907-1993; Garner, James, 1928-2014; O'Brien, Edmond, 1915-1985; White, Robb, 1909-1990 (Warner Home Video, 2006)
A Navy frogman under secret orders is whisked from a stateside romance to the perils of warfare in the South Pacific in 1942.